The Actuarial Conditions for the Valuation of Pension Liability to Become Zero Under Minimum Funding Standard Architecture - Ogungbenle, Gbenga Michael; Omede, David Ilemona (Nepal Journal of Mathematical Sciences, 2022)
Pension valuation exercises for a defined benefit scheme requires an appraisal of both the schemes assets and its liabilities in different circumstances. The valuations are required to comply with regulatory standards, most notably the minimum funding standard. The objectives of this study are: (i) to compute the estimate of minimum funding standard of pension liability (ii) to establish the actuarial condition under which minimum funding standard liability will be zero. This study used minimum funding standard models for the computations of accruing liabilities for the current and past service liability of employees. Data in respects of different categories of employees were collected over 36 employees from a going concern located in Jos South local government of Plateau State in Nigeria. The data includes the employee’s annual salary and their respective demographic data which includes sex, date of birth, date of employment. This was used to determine the number of years of pensionable service completed and the future years of services to be completed before retirement at the age of 65 years. The study also used life annuity table to compute the service liability of each member of the scheme. From the model used, the result shows that the total service liability of the plan will be vanishingly zero when the newly defined annuity component approaches zero hence this represents the condition for liability of the plan to the members to be zero.